ROLE OF WOMEN IN THE SUSTAINABLE MANAGEMENT OF INDIGENOUS WOODLANDS IN MARANGE COMMUNAL LANDS - Chikwature, Whatmore; E, Chikwature (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
This research study sought to determine the role of women in the sustainable management of indigenous woodlands in Manicaland province using Marange communal lands as a point of reference. In this study three traditional leaders, three women’s groups and seventy community women were used as research subjects. Questionnaires were used to gather data from the local women from the three selected villages. Interviews were also used to collect information from traditional leaders and women’s group leaders. These interviews were important in complementing data collected through questionnaires. Field observations were also carried out to enrich the data collected through interviews and questionnaires. The study showed that while women played a vital role in the sustainable management of indigenous woodlands in Marange communal lands, they faced various constraints including greater workload at home with little time to pursue activities outside the family. Therefore the study recommends that since women are more intimately involved with the environment through their day to day activities like fuel wood collection, they should be given due recognition in decision making processes. Finally, it is also recommended that the land tenure system should be redesigned to cater for female heads of households.